PERANCANGAN INSTALASI PENERANGAN PADA KAPAL 12.000 TLC FLOATING DOCK PT. M O S - Hartono; Ilham Gantar Friansyah; Edi kurniawan (JURNAL JALASENA, 2020)
The use of electrical energy in shipping is very important its role as a supporting factor for the smooth operation of the ship itself, for that it needs to be made a very mature design so that the system is able to work effectively and efficiently and be able to overcome the disturbances that occur at any time. Comfort during the process of the operation of the ship and every active'ltas certainly can not be separated from a good lighting system. the main goals and objectives to be achieved in this lighting installation system is that the amount of lighting needed in the operation of the ship can be adequate, sufficient and efficient in its use by not ignoring the safety system both for humans and equipment.